Comparação da perda de calorias provenientes da gordura do leite humano cru de mães de recém-nascidos pré-termo, armazenado em recipientes plásticos e de vidro sob refrigeração - Nogueira, Lorena de Oliveira (2017)
Purpose: Human milk (HM) contains the nutrients necessary for the development of a newborn infant. The feeding of the preterm infants admitted to neonatal units, which does not occur directly from the mother’s breast, implies in the collecting, manipulation, storage and administration of HM. These processes can compromise the nutritional quality of the milk, thus depriving the preterm infants of a significant portion of calories that come its fat content. This study evaluated this loss of calories during the storing of raw human milk (RHM) under refrigeration, in plastic recipients compared to glass recipients, with the aim of understanding the real caloric value being offered to the NBPI while under hospital admission. Methods: This is a cross sectional study, in which 38 mothers of preterm infants participated. The RHM was collected in plastic and glass recipients, which totaled 76 samples. The variables analyzed were the percentage of fat and energy content by using the Creamatocrit method, in triplicate under the following strategy: immediate sample and samples refrigerated for 3, 6, 9 and 12 hours. The multiple comparison of portions was performed using free R software. Results: There was a noted caloric loss in 63.2% of the samples analyzed in the plastic recipients and 57.9% in the glass recipients. However, when fat content (p = 0.366) and caloric value (p = 0.158) were compared between the recipients, there was no significant statistical difference observed. The loss of caloric value total (Kcal/12h) was 676,99 in plastic and 240,37 in glass (p = 0,229). The loss in fat content for the plastic recipient storage group was 2.2 times higher when compared to glass, and in relation to energy, the plastic recipient group presented a loss 2.7 times greater than glass. Conclusion: As there occurred caloric loss in the RHM stored in plastic as well as in the glass recipient, we suggest the RHM is administered to the preterm infants as soon as possible after extraction.